N-Doped Mesoporous Carbons: From Synthesis to Applications as Metal-Free Reduction Catalysts and Energy Storage Materials - Yang, Ying; Gu, Lin; Guo, Shangwei; Shao, Shuai; Li, Zelin; Sun, Yuhang; Hao, Shijie (Frontiers in Chemistry, 2019)
N-doped mesoporous carbons, NMCs, have attracted intensive attention recently and have shown potential applications in various scientific fields including catalysis and energy conversion/storage. Via modification with foreign N elements and construction of mesoporous structures for NMCs, their electronic and spin structure, as well as their porosity can be greatly tailored. And the resultant electron-donor property, surface wettability, conductivity, ion/molecular transfer and reactivity are changed accordingly. In this review, we will summarize the recent research progress of these metal-free NMCs, with an emphasis on their synthesis and performance, especially for their synthetic strategy and catalytic properties towards oxygen and nitro compound reductions, as well as their electrochemical properties as electrode materials for lithium-ion/sulfur batteries and supercapacitors. We hope for future developments, such as controlling doping methods more precisely, generating more active sites by N-doping, and finding wider applications of NMCs in other fields.